Fresno State Women's Softball Team vs. UC Santa Barbara at Old Fenced Field - Watkins, Howard::::::::: (1988)
View from third base side of Fresno State team in field; fans, buildings and trees behind players; Melanie Parrott pitching Note: negative scanned in reverse